2022
DOI: 10.1002/aenm.202103842
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methods for Exploiting Low‐Temperature Heat Sources: Challenges in Material Research

Abstract: stationary non-imaging optics [1] coupled with vacuum tubes and selective adsorbers. [2] ii) Household co-generation or "combined heat and power" generation, that is, the efficient simultaneous room heating and production of electrical current by using fossil fuels, can be performed at household-scale. [3] Household applications involve heat released at low temperature. iii) Low-temperature geothermal heat: Geothermal sources below 100 °C are abundant all over the world [4] and could be tapped by drilling rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…SHVMD can achieve greater water recovery than that achieved by VMD in this study and similar water recovery to that achieved by other larger-scale VMD and thermal desalination processes. However, SHVMD demonstrates higher GOR and energy efficiency than that of conventional VMD, and both GORs and energy efficiencies are comparable to other large-scale VMD and established thermal desalination technologies. , It is expected to have higher water recovery, GOR, and energy efficiency when the stage number is further increased (as shown in Section ) and other operating conditions are optimized. We also compared the specific surface area of membranes and HXs between SHVMD and VMD.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…SHVMD can achieve greater water recovery than that achieved by VMD in this study and similar water recovery to that achieved by other larger-scale VMD and thermal desalination processes. However, SHVMD demonstrates higher GOR and energy efficiency than that of conventional VMD, and both GORs and energy efficiencies are comparable to other large-scale VMD and established thermal desalination technologies. , It is expected to have higher water recovery, GOR, and energy efficiency when the stage number is further increased (as shown in Section ) and other operating conditions are optimized. We also compared the specific surface area of membranes and HXs between SHVMD and VMD.…”
Section: Discussionmentioning
confidence: 98%
“…The capital expense (CapEx) of thermal desalination systems is relatively small compared to the operating expense (OpEx). , HXs and membranes are the two primary components of the CapEx. They are evaluated through two metrics, membrane surface area per liter of produced distilled water and HX surface area per liter of produced distilled water. , In terms of OpEx, the cost of heat dominates . Therefore, all commercially used thermal desalination units rely heavily on heat recovery and reuse in an effort to minimize the injection of new heat into the system, which is also true for MD systems .…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…170 Comprehensive reviews of these electrochemical methods for harvesting low-grade heat can be found in the published literature. 15,171 TIC devices are not included in the comparison due to their fast decay in output power. The typical power density of liquid TGCs ranges from 1 W/m 2 to 10 W/m 2 , while the efficiency is limited by both the heat conduction across the device and the achievable ΔT across the device.…”
Section: ■ Hybrid I-te Devicesmentioning
confidence: 99%